A study on clinicoradiological profile of patients with hydropneumothorax in a tertiary care hospital in Eastern India - Falguni Mandi; Pranab Mandal; Agnishwar Mukherjee; Aparup Dhua; Pinaki Maiti (Asian Journal of Medical Sciences, 2024)
Background: Hydropneumothorax is an abnormal presence of air and fluid in the pleural space. It is a common presentation in the Indian scenario. However, there is a scarcity of studies from Eastern India. Aims and Objectives: The study aimed to evaluate the clinical and radiological presentation, etiological factors, treatment modalities, and outcome of patients of hydropneumothorax. Materials and Methods: Descriptive, observational, cross-sectional study conducted in a tertiary care hospital for 1 year. Adult patients of both genders presenting with a diagnosis of hydropneumothorax were studied. Detailed history and clinical examination were recorded. Chest X-ray, blood, pleural fluid, sputum investigations, and computed tomography (CT) thorax were done. An intercostal drainage (ICD) tube was inserted and the duration of ICD stay was noted. Results: Thirty-six patients were studied. The mean age of presentation is 40.8±14.8 (Mean±SD) years with male predominance. Breathlessness and cough were the most common symptoms (86.1%). Right-sided hydropneumothorax was more common (52.7%). All patients had exudative pleural fluid. Cavity (38.9%) was the most commonly associated radiological finding in CT thorax. Tuberculosis (TB) was the most common etiology (61.1%), followed by acute bacterial infection (36.1%), and malignancy (2.7%). All patients have undergone ICD insertion. About 61.11% of patients had an ICD stay of less or equal to 15 days. Conclusion: Pleural fluid analysis is essential in establishing the etiological diagnosis of hydropneumothorax. TB is the common etiology. ICD insertion along with appropriate chemotherapy are essential components of management.